Community Empowerment through the Cervical and Breast Cancer Early Detection Program with the Formation of Srikandi Cadres (Early Cancer Awareness) in Kangean Islands, Sumenep Regency - Ika Mustika; Esti Tyastirin; Moch. Irfan Hadi; Irul Hidayati (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
Cervical cancer and breast cancer are two types of cancer that often occur in women and contribute to a high mortality rate. However, there are still many people who do not know about the early detection of cervical cancer and breast cancer to prevent diseases. This community service aims to make people aware of the dangers of breast and cervical cancer. The subjects of this community service program assistance were women in Arjasa sub-district, Kangean Islands, Sumenep Regency. The method used in community service is Community-based Research (CBR) to develop early detection programs for non-communicable diseases of breast cancer and cervical cancer. Research findings showed 91.1% of respondents did not know about early detection of IVA test. The results of the IVA screening test on 90 respondents, there is one respondent with a definite IVA pre-cancerous lesion. SRIKANDI (Sadar Kanker Sejak Dini) Cadre was formed to increase public awareness. Srikandi's cadre provisioned with knowledge about cervical and breast cancer, equipped with pocketbooks and given training on breast self-examination (BSE). They invited the public to increase awareness of cervical and breast cancer by conducting IVA tests and being able to do breast self-examinations to reduce the incidence of cervical and breast cancer.